Proliferating Tricilemmal Cyst: Case Report - Dagli, A. Ferda; Akatli, Aysenur; Sahin, Nurhan; Ucer, Ozlem; Kilicarslan, Ahmet; Artas, Gokhan (Galenos Yayincilik, 2015)
Proliferating trichilemmal cyst is slowly growing benign cutaneous adnexal tumor of the hair follicle. Proliferating trichilemmal cysts are seen usually on the scalp and in elderly women. We present pathological findings of 43 years-old female patient with scalp nodular lesion with the literature.
Prolifere trikilemmal kist: Olgu sunumu
Keywords: Hair follicle; proliferating tricilemma lcyst; cutenous adnexal tumor; scalp; histopathology; sebaceous cyst